Numerical solution of eight order boundary value problems using Chebyshev polynomials - Musiliu Tayo Raji; Christie Yemisi Ishola; Olayemi Olutola Babalola; Tawakalt Abosede Ayoola; Nasiru Muhammed Momoh; Olumuyiwa James Peter (Mathematics and Computational Sciences, 2023)
First-kind Chebyshev polynomials are used as the basis functions in this study to present the approximations to the eighth-order boundary-value problems. The problem is reduced using the suggested approach into a set of linear algebraic equations, which are then solved to determine the unknown constants. To demonstrate the application and effectiveness of the strategy, analytical results are provided using tables and graphs for three examples. The results obtained using the proposed method reveal that it is simple and outperforms comparable solutions in the literature.